The Mitochondrial DNA Control Region Might Have Useful Diagnostic and Prognostic Biomarkers for Thyroid Tumors - GÖZÜ, HÜLYA (JOHANN AMBROSIUS BARTH VERLAG MEDIZINVERLAGE HEIDELBERG GMBH, 2019)
The literature suggests that mitochondrial DNA (mtDNA) defects are associated with a large number of diseases including cancers. The role of mtDNA variations in thyroid cancer is a highly controversial topic. Therefore, we investigated the role of mt-DNA control region (CR) variations in thyroid tumor progression and the influence of mtDNA haplogroups on susceptibility to thyroid tumors. For this purpose, in total, 108 hot thyroid nodules (HTNs), 95 cold thyroid nodules (CTNs), 48 papillary thyroid carcinoma (PTC) samples with their surrounding tissues and 104 healthy control subjects' blood samples were screened for all mtDNA CR variations using Sanger sequencing. We found that MtDNA haplogroup U was significantly associated with susceptibility to benign thyroid entities. In addition, eight single nucleotide polymorphisms (SNPs) (T146C, G185A, C194T, C295T, G16129A, T16304C, A16343G and T16362C) in the mtDNA CR were associated with the occurrence of benign and malign thyroid nodules in the Turkish population. As compared with samples taken from a healthy Turkish population and HTNs, the frequency of C7 repeats in D310 polycytosine sequence was found to be higher in CTNs and the PTC samples. In addition, the frequency of somatic mutations in mtMSI regions including T16189C and D514 CA dinucleotide repeats were found to be higher in PTC samples than benign thyroid nodules. Conversely, the frequency of somatic mutations in D310 was found to be higher in HTNs than CTNs and PTCs. In conclusion, mtDNA D310 instability does not play a role in the tumorigenesis of PTC but the results indicate that it might be used as a diagnostic clonal expansion biomarker for premalignant thyroid tumor cells. In addition, D514 CA instability might be considered as a prognostic biomarker for benign to malign transformation in thyroid tumors.
Keywords: mitochondrial DNA; control region; D310; D514 CA repeat; T16189C; thyroid nodule; papillary thyroid cancer; D-LOOP REGION; MOLECULAR PATHOGENESIS; MUTATIONS; NODULES; INSTABILITY; RECEPTOR; IDENTIFICATION; POLYMORPHISMS; POPULATION; EVOLUTION